The Development of a Conceptual Framework and Preliminary Item Bank for Childbirth‐Specific Patient‐Reported Outcome Measures. (24th May 2018) - Korst, Lisa M.; Fridman, Moshe; Saeb, Samia; Greene, Naomi; Fink, Arlene; Gregory, Kimberly D.
Abstract : Objective: To develop a conceptual framework and preliminary item bank for childbirth‐specific patient‐reported outcome (PRO) domains. Data Sources: Women, who were U.S. residents, ≥18 years old, and ≥20 weeks pregnant, were surveyed regarding their childbirth values and preferences (V&P) using online panels. Study Design: Using community‐based research techniques and Patient‐Reported Outcomes Management Information System (PROMIS ® ) methodology, we conducted a comprehensive literature review to identify self‐reported survey items regarding patient‐reported V&P and childbirth experiences and outcomes (PROs). The V&P/PRO domains were validated by focus groups. We conducted a cross‐sectional observational study and fitted a multivariable logistic regression model to each V&P item to describe "who" wanted each item. Principal Findings: We identified 5, 880 V&P/PRO items that mapped to 19 domains and 58 subdomains. We present results for the 2, 250 survey respondents who anticipated a vaginal delivery in a hospital. Wide variation existed regarding each V&P item, and personal characteristics, such as maternal confidence and ability to cope well with pain, were frequent predictors in the models. The resulting preliminary item bank consisted of 60 key personal characteristics and 63 V&P/PROs. Conclusions: The conceptual framework and preliminary (PROMIS ® ) item bank presented here provide a foundation for the development of childbirth‐specific V&P/PROs.